Critical Discourse Reveals Educational System Problems in Indonesian Podcast: Diskusi Kritis Mengungkap Permasalahan Sistem Pendidikan di Podcast Indonesia - Nick Samudra; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Digital media, particularly podcasts, have become important platforms for public discussion and educational discourse. Specific Background: The podcast “Guru Gembul Bongkar Sistem Pendidikan Indonesia, Anak Sekolah Trauma Belajar!” on Tom Mc Ifle’s YouTube channel presents criticism of structural problems in Indonesian education, including formal schooling and parental roles. Knowledge Gap: Limited studies examine educational criticism in podcast media using Teun A. van Dijk’s discourse analysis covering textual, social cognition, and social context dimensions. Aims: This study analyzes educational criticism presented in the podcast using Van Dijk’s discourse framework. Results: The analysis identifies macro, superstructure, and micro textual elements, including themes, structural organization, background, intention, coherence, lexicon, and metaphor, which portray educational practices as restricting student potential and contributing to learning trauma. Social cognition analysis shows media narratives shaping public understanding, while social context findings indicate that the creator’s popularity supports wider public awareness of educational issues. Novelty: This research applies Van Dijk’s multidimensional discourse model to examine educational criticism in Indonesian podcast media. Implications: The findings demonstrate that podcasts function as discursive platforms that encourage public reflection on educational practices and highlight the role of parental support in developing children’s natural abilities. Highlights: Multi-Layer Discourse Structure Demonstrates Narratives Describing Limitations Within Current Schooling Practices. Social Cognition Dimension Shows Media Storytelling Shaping Public Understanding of Student Learning Experiences. Social Context Dimension Reveals Wide Audience Reach Supporting Dissemination of Educational Reform Narratives. Keywords: Critical Discourse Analysis, Podcast Media, Indonesian Education System, Teun A. Van Dijk, Educational Criticism